READING TEXT POPULAR SONG INDONESIA: STUDY SEMIOTIC-HEURISTIC - Widawati, Rika (EDUTECH, 2015)
Abstract. This paper is the result of the research that based on the phenomenon in Indonesia today. The texts of Indonesian popular songs that part of the literature which create new vocabularies or make the modification of old language. The structure of this work seems to be odd. It means the new vocabulary is different from the standard of Indonesian structure. The aim of this descriptions are the correction of (1) the mistake of the phenomenon in the text of Indonesian popular songs (2) the meaning of indonesian popular songs must be based on reading of semiotics and heuristic.Â  To describe this purpose, we use semiotic theory and structuralism. While the sources of this research are adopted from the texts of Indonesian popular songs which are published in 2000-2010 periode. Both Indonesian popular songs, either good songs or odd songs which has the value of good literature, namely which consist of good structure, poetic, romantic with symbolic style. Heuristically readings of the two text Indonesian songs indicate violations of linguistic rules either syntagmatic, paradigmatic, meaningfulness relations and composition.Keywords: the text of Indonesian popular song, semiotic, heuristicAbstrak. Tulisan ini merupakan hasil penelitian yang didasari oleh fenomena bahwa dewasa ini teks lagu populer Indonesia sebagai bagian dari karya sastra banyak menampilkan kosakata baru ataupun modifikasi kosakata lama, dengan komposisi yang dipandang â€œmenyimpangâ€ dari kaidah tata bahasa baku maupun konvensi sastra. Tulisan ini bertujuan untuk mendeskripsikan (1) fenomena struktur kebahasaan dalam teks lagu populer Indonesia dan (2) makna teks lagu populer Indonesia berdasarkan pembacaan semiotik-heuristik. Untuk mendeskripsikan hal tersebut digunakan teori semiotik dan strukturalisme. Sementara sumber data penelitian ini adalah teks lagu populer Indonesia tahun 2000 â€“ 2010. Baik lagu-lagu yang dipandang menyimpang dari kaidah atau konvensi sastra maupun sebaliknya, yakni lagu-lagu yang sesuai kaidah-kaidah bahasa dan sastra, yaitu yang bernilai puitis, romantis, dengan gaya bahasa simbolis. Hasil pembacaan secara heuristik terhadap teks dua lagu Indonesia menunjukkan adanya pelanggaran kaidah linguistik baik secara sintagmatik, paradigmatik, kebermaknaan relasi dan komposisinya.Â Kata Kunci : teks lagu populer Indonesia, semiotik, heuristik